A framework for pharmaceutical value-based innovations. (January 2012) - Salimi, Tehseen; Lehner, Jean-Pierre; Epstein, Robert S; Tunis, Sean R
The rapidity of change and increasing complexity of today''s healthcare environment dictates that pharmaceutical companies refine their drug development process to ensure that products provide maximal value to consumers. Innovation should receive the support and encouragement it deserves but the balance between cost of therapy and enhanced benefits to the end users, the patients, must not be compromised. The health or quality-of-life outcomes that therapies are likely to achieve need to be clearly stated for patients so they know what to expect before beginning treatment. A drug development program that incorporates principles of 'patient-centered medicine'' early on can help define the true value of a health technology. This demands not only demonstrating value as measured by actual patient experience and patient-reported outcomes, but understanding the unmet needs of multiple stakeholders: what is their perception of what represents value? What factors impact healthcare coverage decisions? In this paper, we describe an illustrative framework designed to weave 'patient-centric'' medical and real-world evidence into the phases of research and development. This evidence and value development framework works iteratively, providing useful insights parallel to product development from early phase to life-cycle management while forming a progressive evidence chain throughout the phases of research and development. This in turn leads to the creation of value-based innovation with robust foundational evidence for clinical decisions, postlaunch coverage and reimbursement evaluations.